Role Skill Development Revolving Fund In Optimizing The Competitiveness of Vocational School Graduates Through Developmentvocational Carrier and Professional Competence - Rosidawati Nur, Dewi; Dwi Suseno, Bambang; Ika Sari, Gema (International Journal of Science and Environment (IJSE), 2025)
The low competitiveness of vocational high school (SMK) graduates remains a serious challenge in meeting the needs of the dynamic industrial world, particularly in Banten Province, particularly Cilegon City. Although this region has many companies in the manufacturing, shipping, and stevedoring sectors, the unemployment rate among vocational high school graduates remains relatively high. This study aims to analyze the impactSkill Development Revolving Fundtowards developmentvocational careerand professional competence in an effort to increase the competitiveness of vocational school graduates. The research approach used was quantitative with a sample of 266 respondents, who were randomly drawn from graduates of four vocational schools in Cilegon City. The results of the study showed that: (1)Skill Development Revolving Fundhas a significant impact on developmentvocational career, which ultimately increases the competitiveness of vocational school graduates; (2)Skill Development Revolving Fundalso has a significant influence on improving the professional competence of graduates, thus encouraging the creation of competitive advantages; (3) overall,Skill Development Revolving Fundand its indicators play an important role in strengthening the competitiveness of vocational school graduates; and (4) a combination ofSkill Development Revolving Fund, developmentvocational career, and professional competence provide a positive contribution to increasing the competitiveness of vocational school graduates. Thus, it can be concluded that the management ofSkill Development Revolving FundAn effective program can create career development mechanisms and enhance professional competencies relevant to industry needs. This program needs to be continuously strengthened as a sustainable strategy to prepare a competent, adaptive, and highly competitive vocational high school workforce in the global job market.